Investigation of strength of shaped elements of the main gas pipeline - Doroshenko, Ya.V. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2019)
The research has been carried out for the purpose of a complex numerical three-dimensional modeling of the stressed state of taps and tees of main gas pipelines taking into account the gas-dynamic processes occurring in these shaped elements and the temperature difference in their walls. A 3D modeling of the elbow with a 90° angle and a reinforcing pad on the main line and the drainage of the passage line of the trunk of the main gas pipeline has been carried out. There has been studied the gas flow with 3D models of shaped elements of the main gas pipeline by means of the CFD modeling. The simulation has been рerformed for the equidistant tees in which the entire flow from the main stream flows into its branch. The mathematical model is based on the solution of the Navier–Stokes equation system, continuity equation, closed by a two-parametric k -e model of the Launder–Sharma turbulence with corresponding initial and boundary conditions. The simulation results are visualized in the ANSYS Fluent R18.2 Academic Postprocessor by constructing the pressure fields on the contours and in the longitudinal and transverse sections of shaped elements. The exact values of pressure at different points of the inner cavity of the shaped elements have been determined, the places of rise and fall of pressure identified. There have been performed the simulation of the temperature difference in the walls of the drainage, the trunk of the main gas pipeline in the module ANSYS Transient Thermal. The results of CFD and temperature modeling were imported into the mechanical module ANSYS Static Structural, where the finite element method was used to simulate the stressed state of the shaped elements of the main gas pipeline, taking into account the gas-dynamic processes occurring in their internal cavity and the temperature difference in the walls. The results of the simulation have been visualized by constructing a three-dimensional color fields of equivalent von Mises stresses in the tee and in the elbow. The places of the maximum equivalent stresses in the wall of the studied shaped elements have been revealed.